Positive teacher-student relationships may lead to better teaching. (August 2022) - Li, Xintong; Bergin, Christi; Olsen, Amanda A.
Highlights: Positive teacher-student relationships promote complex teaching practices. Teacher-student relationships more strongly affect teaching in higher grade levels. Affectively engaging students may result in positive teacher-student relationships.